Odpowiedzi

2010-03-04T21:01:53+01:00
20b + 6c=2(10b+3c)
25a-5=5(5a-1)
1,4a-7=1,4(a-5)
0,6a+0,6=0,6(a+1)
22b+6=2(11b+3)
0,9b+12=3(0,3b+4)
0,4-0,2b=2(0,2-0,1b)
2,5+0,5b=0,5(5+b)

sorki ale nie wiem o co w tym chodzi:
2 2
2 - a +2 - =
5 5

1 5
- b+ - =
6 6
2010-03-04T21:04:46+01:00
20b + 6c= 2(10b +3c)
25a-5= 5(5a - 1)
1,4a-7= 7(0,2a-1)
0,6a+0,6= 0,6(a+1)
22b+6= 2(11b+3)
0,9b+12= 3(0,3b+4)
0,4-0,2b= 0,2(2-b)
2 - a +2 - = 2(1+1)-a
2,5+0,5b= 0,5(5+b)


niestety nie wiadomo o co w reszcie chodzi
2010-03-04T21:06:50+01:00
20b + 6c=2(10b+3c)
25a-5=5(5a-1)
1,4a-7=7(0,2a-1)
0,6a+0,6=0,6(a+1)
22b+6=2(11b+3)
0,9b+12=3(0,3b+4)
0,4-0,2b=0,2(2+b)
2 2
2 - a +2 - =2-2/5a+2-2/5=2-0,4a+2-0,4=04(5-a+5-1)
5 5

1 5
- b+ - =1/6(b-5)
6 6

2,5+0,5b=0,5(5+b)
2 5 2